Embedded formative feedback in chemistry worksheets: a self-regulation approach to conceptual learning of the periodic table of elements - Jihan Nabilah Rahma; Muchlis Muchlis (Journal of Counseling, Education and Society, 2026)
This study aims to investigate the effectiveness of Student Worksheets (LKPD) oriented toward Assessment for Learning (AfL) in improving student learning outcomes on the Periodic Table of Elements (PTE) topic. The research employed a pre-experimental design with a one-group pretest-posttest model (O₁ X O₂), conducted with students in Grade X of SMA 2 Muhammadiyah Sidoarjo, Indonesia. Grounded in Black and Wiliam’s (1998) Assessment for Learning (AfL) framework and self-regulated learning theory, the worksheets embedded five core AfL mechanisms transparent learning objectives, continuous evidence elicitation, constructive feedback loops, peer assessment activities, and structured self-assessment checkpoints hypothesized to address known conceptual barriers in Periodic Table learning by enabling students to monitor, evaluate, and regulate their own comprehension in real time. Data were collected through validated pretest and posttest instruments measuring conceptual understanding of the PTE. A paired sample t-test, preceded by Shapiro-Wilk normality testing, was applied to examine score changes. Results revealed a mean improvement of 41.79 points (pretest M = 42.07; posttest M = 83.86), with a t-value of −22.476 (p < 0.05) and an N-Gain of 0.72 (High category). These findings confirm that formative feedback embedded within chemistry worksheets produces substantive gains in conceptual understanding, with theoretical implications for self-regulation-based instructional design in secondary science education.